Towards a complete human cell atlas: a single-nucleus RNA sequencing study of the paediatric and adult human brain - Steyn, Christina (Department of Human Biology, 2024)
Postnatal human brain maturation from birth to early adulthood represents a period of susceptibility for neuropsychiatric risk. While temporal gene expression dynamics over this period have been studied extensively, there are no studies exploring the paediatric brain at single cell resolution. To address this, we present the first paediatric brain cell atlas comprising of 6 single nucleus RNA sequencing (snRNA-seq) datasets generated from antemortem human brain tissue samples obtained during elective surgeries to treat epilepsy. To complement these, we included 6 snRNA-seq datasets from adult brain tissue. The 12 samples are all of temporal cortex origin and were produced using the 10X Genomics Single Cell 3' gene expression analysis kits. The datasets were processed using an optimised pipeline and the nuclei were annotated into various cell types using the Allen Institute's middle temporal gyrus dataset as a reference. A novel machine learning method was applied to the annotated datasets to identify combinations of marker genes capable of distinguishing each cell type. Based on this, several minimal marker genes were identified which were shared between paediatric samples and not adults or vice versa. Three different tools were used to identify genes changing in their level of expression with age within each cell type. This revealed hundreds of differentially expressed genes (DEGs), with numerous DEGs being unique to specific cell types and subtypes. From these analyses, two long noncoding RNAs of interest were selected for further in silico characterization which revealed putative functions for these genes. Overall, we have provided a resource which can be interrogated further to explore differences between paediatric and adult samples at the gene expression and cell level. This may promote an expansion in our understanding of brain maturation and brain diseases.